Bidirectional Relationship Between Tuberculosis and Hypothyroidism: An 18-Year Nationwide Population-Based Longitudinal Cohort Study - Cheng, Li-Ting; Chung, Chi-Hsiang; Peng, Chung-Kan; Shu, Chin-Chung; Wu, Shu-Yu; Wang, Sheng-Huei; Wu, Gwo-Jang; Tsao, Chang-Huei; Sun, Chien-An; Chien, Wu-Chien; Tang, Shih-En (Frontiers in Medicine, 2022)
Some antituberculosis agents may cause hypothyroidism, and thyroid hormones play a vital role in Mycobacterium tuberculosis infection. However, the relationship between tuberculosis (TB) and hypothyroidism has not been clearly established. Therefore, this retrospective, longitudinal cohort study aimed to investigate the association between these two diseases using the 2000–2017 data from the Taiwan's National Health Insurance Research Database. The hypothyroidism and TB cohorts were matched with the control group in a 1:4 ratio. Adjusted hazard ratios (aHRs) were assessed using Cox proportional hazards regression analysis in each cohort. In total, 3,976 individuals with hypothyroidism and 35 120 individuals with TB were included in this study. The risk of developing TB in patients with hypothyroidism was 2.91 times higher than that in those without hypothyroidism (95% confidence interval [CI], 1.50–3.65). The subgroup of thyroxine replacement therapy (TRT) had a 2.40 times higher risk (95% CI, 1.26–3.01), whereas the subgroup of non-TRT had a 3.62 times higher risk of developing TB than those without hypothyroidism (95% CI, 2.19–4.84). On the other hand, the risk of developing hypothyroidism in patients with TB was 2.01 times higher than that in those without TB (95% CI, 1.41–2.38). Our findings provide evidence that TB and hypothyroidism are interrelated. Thus, clinicians and public health authorities should monitor the association between these two diseases to reduce the relevant disease burden.